The Calcutta chromosome a novel of fevers, delirium & discovery - Ghosh, Amitav (Brilliance Audio on compact disc, 2010)
While working his mundane job at a huge corporation in a not-too-distant future New York City, Antar discovers evidence behind the disappearance of a man who was investigating a malaria cure in Calcutta.